Ecological patterns of Fontinalis antipyretica and Fontinalis hypnoides distribution in Bulgarian rivers, and relevance to ecological status assessment - Gecheva, Gana; Natcheva, Rayna; Ganeva, Anna (Frontiers in Environmental Science, 2025)
The Water Framework Directive (WFD) initiated an extensive survey of European surface waters and their biological communities. In Bulgaria, aquatic macrophytes were included in the ecological status assessment for the first time in 2009 through the adaptation of the Reference Index, which reflects the influence of multiple stressors. Aquatic bryophytes constitute a significant component of the indicator taxa, with the genus Fontinalis, being the most widespread. Two species of the genus, F. antipyretica and F. hypnoides, have been assigned to different ecological groups: the former to indifferent (group B), and the later to reference indicators (group A). The distribution, abiotic and biotic preferences of these two species were studied in order to refine the macrophyte-based Reference Index and broaden the knowledge on the ecology of the species. Three datasets were used: 421 detailed field survey records conducted between 2009 and 2024, 21 literature sources with 73 records, and 43 herbarium records. Only field survey data were used to compare percent distribution and conduct ecological analyses, as literature and herbarium records are not directly comparable due to differing sampling methods and temporal coverage. Fontinalis antipyretica records appeared to be 11% from the field survey database, while F. hypnoides had distribution at only four river sites (1%). Fontinalis antipyretica exhibits greater ecological amplitude, including tolerance for higher elevations and broader flow conditions. It also exhibits a broader distribution in physico-chemical characteristics of the river water: conductivity (31.3–4,380 μS cm-1) and total nitrogen (TN, 0.07–3.3 mg L-1), consistent with its ecological generalism. Fontinalis hypnoides, although based on fewer samples, displays narrower distributions, particularly in pH and TN (<1 mg L-1) - supporting its sensitivity to physico-chemical parameters. This finding is promising regarding its allocation as an indicator of reference conditions. The overlap in co-existing species indicates a certain degree of ecological similarity between the two Fontinalis species, reflecting their preference for similar aquatic macrophyte assemblage types.